Ownership Structure, Board Characteristics, Dan Dividen Policy Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Intan Nurwanti; Tiara Putri Hendrian; Rifati Nabila; Henny Setyo Lestari (Jurnal Ekonomi, 2022)
This study aims to determine the effect of ownership structure, board characteristics on dividend policy. The research sample is a manufacturing company listed on the Indonesia Stock Exchange for the 2016-2020 period. The independent variables are institutional ownership, ownership concentration, board of directors size, female board of directors ratio, independent board ratio, the dependent variable is dividend policy and the control variables are company age, firm size, financial leverage, return on assets (ROA). The number of samples in this study was 30 manufacturing companies using the purposive sampling technique. Panel data regression shows that the size of the board of directors, the ratio of the board of directors has a positive effect on dividend policy, institutional ownership, ownership concentration, the ratio of independent boards has no effect on dividend policy. It is hoped that the research results will provide input for companies and investors to consider institutional ownership, the concentration of ownership, size of the board of directors, the ratio of women's board of directors, and the ratio of independent boards because they have an influence on dividend policy.